Workplace Violence Against Emergency Versus Non-Emergency Nurses - Naif Abdulaziz Nawi Alonazi, Abdullah Hulayyil Shaya Alotaibi, Majed Khidhran Kani Almutairi, ‏Faisal Matar Olaywi Alghashmari, Ahmad Yahya Maqwi Duraib , Nashmi Olian Mosallm Almotairi, Galib Falih Gazai Alotaibi, Abdulaziz Jahz Gufain Almotairi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Workplace violence (WPV) against nurses is a significant yet often overlooked issue . This research aims to estimate the prevalence and identify associated risk factors of various types of violence against nurses , focusing on differences between those working in emergency departments and non-emergency clinics. The study utilizes a cross-sectional comparative design, collecting data through an adapted self-administered questionnaire developed by reputable organizations in the field. Results highlight the circumstances of violence, types of perpetrators involved, and nurses' responses to such incidents. Findings indicate that all types of WPV are prevalent among nurses, with factors like emergency specialty, work shifts, and younger age contributing to higher risk. The study underscores the urgent need for policies and interventions to address and mitigate workplace violence in healthcare settings